The Effect of Weekend Work on Shared Leisure Time - Crawley, Thomas (My University, 2021)
Using panel data from the Household, Income and Labour Dynamics in Australia (HILDA) Survey, I estimate the effect of weekend work on five measures of shared leisure time. Binary and ordered probit estimates indicate that weekend work has a negative association with all five measures. Fixed effects estimates suggest that weekend work has a negative effect on work–family balance and the probability of club membership, but no significant effect on the frequency of social time, attendance at community events or attendance at religious services.
Australian Economic Review
Keywords: Labour market; Lifestyle; Social engagement